Objek Wisata Pura Tirta Empul Sebagai Media Pendidikan Multikultural Bagi Generasi Milenial Pada Era 4.0 - Ni Wayan Karmini; Ni Putu Dyatmikawati; Gusti Ayu Ayu Suasthi; Ni Ketut Srie Kusuma Wardhani; Gede Yoga Kharisma Pradana (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2020)
This scientific work discusses the existence of the tourism object Tirta Empul as a venue for the economic development of local communities, as well as a multicultural education media for millennials in the 4.0 era. This paper is the result of qualitative research. Data was collected through observation, literature study and in-depth interviews with 11 informants managing Tirta Empul attractions, observers of Balinese culture and tourists visiting Tirta Empul attractions. Data analysis was conducted descriptively-interpretative by applying the theory of tourism development and the theory of commodification. The results of the study show that through promotion in the 4.0 era cybermedia network, the tourism objects of Tirta Empul are increasingly known by local and foreign tourists. Commodification of tourism objects Tirta Empul has aroused manners of entrepreneurship and supports the development of the local Indigenous Village. In addition, the cultural tourism object of Tirta Empul is also a special multicultural education media for millennials. Tourism activities in Tirta Empul that are able to generate social-economic activities and foster multicultural awareness need to be maintained and developed.